High-Fat Mouse Model to Explore the Relationship between Abnormal Lipid Metabolism and Enolase in Pancreatic Cancer - Lin Qin; Kai Sun; Li Shi; Yushan Xu; Rongping Zhang (Mediators of Inflammation)
Malignant tumors have become a major social health problem that seriously threatens human health, among which pancreatic cancer has a high degree of malignancy, difficult diagnosis and treatment, short survival time, and high mortality. More and more attention has been paid to abnormal lipid metabolism as a momentous carcinogenesis mechanism. Here, we explored the relationship between abnormal lipid metabolism, enolase, and pancreatic cancer by clinical data analysis. A high-fat mouse model was constructed, and then, a subcutaneous tumorigenesis mouse model of carcinoma of pancreatic cells and a metastatic neoplasm mouse pattern of pancreatic carcinoma cells injected through the tail vein were constructed to explore whether abnormal lipid metabolism affects the progression of pancreatic cancer in mice. We constructed a high-lipid model of pancreatic carcinoma cell lines and knockdown and overexpressed enolase in pancreatic carcinoma cell lines and investigated whether high lipid regulates epithelial-mesenchymal transition (EMT) by upregulating enolase (ENO), thereby promoting the cells of pancreatic carcinoma to invade and migrate. Triglycerides, total cholesterol, free cholesterin, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and neuron-specific enolase (NSE) from pancreatic cancer patients and nonpancreatic cancer patients were tested. The differences in blood lipids between patients with and without pancreatic carcinoma were compared, and the correlation between blood lipids and neuron-specific enolase was analyzed. We confirmed that the serum triglyceride level of pancreatic cancer patients at initial diagnosis is overtopping nonpancreatic cancer patients, and the neuron-specific enolase level of patients with pancreatic carcinoma is better than nonpancreatic carcinoma sufferers. Triglyceride level is positively correlated with neuron-specific enolase level, and serum triglyceride level has predictive value for pancreatic cancer. Hyperlipidemia can promote tumor growth and increase the expression levels of ENO1, ENO2, and ENO3 in subcutaneous tumor formation of pancreatic cancer in mice. Additional hyperlipidemia promoted pancreatic carcinoma metastasis in the lung in mice injected through the tail vein, which confirmed that hyperlipidemia accelerated the process of EMT by increasing the expression of ENO1, ENO2, and ENO3, therefore promoting the pancreatic cancer cell metastasis.